1996
DOI: 10.1080/00480169.1996.35932
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of mastitis in primiparous heifers in eleven Waikato dairy herds

Abstract: The objective of the study was to determine the prevalence of mastitis among primiparous heifers at calving and at drying off in 11 Waikato dairy herds during the 1993-94 dairy production season. Duplicate quarter milk samples were collected aseptically from 458 heifers within 5 days after calving for bacteriological analysis. Mastitis was diagnosed in at least one quarter in 35.6% of these heifers. Coagulase-negative staphylococci were isolated from 21.8% of the heifers. The prevalence of coagulase-negative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 8 publications
3
21
2
Order By: Relevance
“…An increasing prevalence of S. uberis mastitis has been reported, with approximately 14 to 26% of clinical cases in Canada, the United States, The Netherlands, and the United Kingdom being due to this pathogen (3,9). S. uberis is also highly prevalent in Australia and New Zealand, where the dairy industry is mainly pasture based (13,14). A recent report from New Zealand indicated that over 30% of all clinical mastitis was due to this organism (5).…”
mentioning
confidence: 99%
“…An increasing prevalence of S. uberis mastitis has been reported, with approximately 14 to 26% of clinical cases in Canada, the United States, The Netherlands, and the United Kingdom being due to this pathogen (3,9). S. uberis is also highly prevalent in Australia and New Zealand, where the dairy industry is mainly pasture based (13,14). A recent report from New Zealand indicated that over 30% of all clinical mastitis was due to this organism (5).…”
mentioning
confidence: 99%
“…With respect to the prevalence of environmental streptococcal mastitis, a large proportion of variability in its incidence and, both between geographical locations and within a single herd, can be ascribed to a number of independent variables such as season of the year, stage of lactation, parity, and various management practices (Hogan et al, 1989;Pankey et al, 1996;Hogan & Smith, 2003). Streptococcus agalactiae is one of the obligate pathogen of mammary gland in case of bovines, colonizing the teat canal (Dodd, 1983).…”
Section: Resultsmentioning
confidence: 99%
“…Areas under shade trees can produce conditions of high exposure and pastures that are over grazed or grazed during periods of heavy rain may also lead to conditions of exposure similar to housed cattle. The environmental streptococci are the most significant environmental pathogen in New Zealand dairy herds where cows spend virtually 100% of there time on pasture (38,54). Additional research on the association between pasture conditions and teat contamination with environmental pathogens would be beneficial.…”
Section: Exposurementioning
confidence: 99%
“…The prevalence of intramammary infections (IMI) and incidence of clinical mastitis have been measured in a host of surveys during the last 25 years. Environmental streptococci have consistently been reported as a leading cause of both subclinical and clinical mastitis throughout the world (11,24,38,51,55). A large proportion of variability in incidence and prevalence of environmental streptococcal mastitis, both between geographical locations and within a single herd, can be ascribed to a number of independent variables identified in these surveys.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation